Treatability of drinking water parameters from Kerian River by using carbon-mineral composite: Batch mechanisms and characterization study - Kamaruddin M.A.; Yusoff M.S.; Nordin M.F.M.; Zawawi M.H.; Alrozi R. (American Institute of Physics Inc., 2023)
There are many treatment processes over the world on river water. However, the simple and low cost technologies are quite limited. Therefore, the purpose of this study is to examine the turbidity, colour, pH, Total Dissolved Solid (TSS), Iron and Manganese from selected river water by a combination of activated carbon, limestone and polyvinyl alcohol which produces a composite media. The analyses for the parameters removal efficiency are conducted by using statistical analysis two ways Analysis of Variance (ANOVA). In batch study, the removal efficiency of all the mixture of composite media indicated the composite adsorbent could remove more than 50% of raw water contaminants which complies to National Drinking Water Quality Standard, 2000. The optimum mixing ratio of hydrophobic: hydrophilic is 1:7 and 1:2 which is 875.0g and 667.0g limestone, 125.0 g and 333.0 g activated carbon (AC) and water 375 ml with highest removal percentage for turbidity (91.86%), colour (93.44%), TSS (91.27%), iron (98.49%) and manganese (98.18%). The study indicated that the composite material has a good potential for further research and future application. 2017 Author(s).